Red, White, and Blue Letter Days : An American Calendar - Dennis, Matthew, 1955- (Book collections on Project MUSE., 2002)
The Fourth of July, Thanksgiving, Washington's Birthday, Memorial Day, Columbus Day, Labor Day, Martin Luther King's Birthday, and other celebrations matter to Americans and reflect the state of American local and national politics. Commemorations of cataclysmic events and light, apparently trivial observances mirror American political and cultural life. Both reveal much about the material conditions of the United States and its citizens' identities, historical consciousness, and political attitudes. Lying dormant within these festivals is the potential for political consequence, controversy, even transformation. American political fetes remain works in progress, as Americans use historical celebrations as occasions to reinvent themselves and their nation, often with surprising results. In six engaging chapters 'assaying particular political holidays over the course of their histories, Red, White, and Blue Letter Days examines how Americans have shaped and been shaped by their calendar. Matthew Dennis explores this vast political and cultural terrain, charting how Americans defined their identities through celebration. Independence Day invited African Americans to demand the equality promised in the Declaration of Independence, for example, just as Columbus Day-celebrating the Italian, Catholic explorer-helped immigrants proclaim their legitimacy as Americans. Native Americans too could use public holidays, such as Thanksgiving or Veterans Day, to express dissent or demonstrate their claims to citizenship. Merchants and advertisers colonized the American calendar, moving in to sell their products by linking them, often tenuously, with holiday occasions or casting consumption as a patriotic act.